TEACHERS’ PERCEPTION TOWARD THE IMPLEMENTATION OF STUDENTS CENTERED METHOD IN COMPARISON TO TEACHERS CENTERED METHOD IN THE SECONDARY SCHOOL IN RIAU PROVINCE. - Erni, Erni (SOROT, 2012)
The objective of the study was to know the teachers perception toward theimplementation of Students Centered Method ( SCM) in comparison to TeacherCentered Method(TCM) to the secondary school studentsRiau province. Thesubject of the study was 28 the secondary school teachers of six regencies in Riauprovince.The result of the study indicated that English teachers moderately to highlysupported the implementation of SCM in teaching reading. They showed theirgreater agreement to SCM method than TCM in terms of conditional, conceptual ,instructional, and students - learning perspectives. The comparison of teachers’perception toward the implementation of SCM were significantly greater than theirperception toward TCM in teaching reading. For classroom assessment, grammarand vocabulary mastery, and content learningfor instructional perspectivesdimension and memorizing strategy and everyday reading habit for studentslearning perspectives dimension, teachers showed positive perspective to TCMthan to SCM but there was no significant differences on means value of bothmethods. Lastly, there were no significant differences on teachers perceptionregarding their, ages, sex, education except for those teaching experiences above20 years but with no significantly differed on mean value of both .Keywords: perception, student centered method, teacher centered method